High-strength heat-conducting insulating sealant capable of being quickly dried and cured on surface and preparation method of high-strength heat-conducting insulating sealant

By synergizing the modified organic tin catalyst with mesoporous materials and organic ligands, the cross-linking network is optimized, the performance defects of silicone sealants are solved, and a high-strength thermally conductive insulating sealant with rapid surface drying and curing is achieved to meet the heat dissipation and insulation needs of electronic equipment.

CN120758225APending Publication Date: 2025-10-10TANGSHAN SANYOU CHEM IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510913423.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-03
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing silicone sealants have performance defects in weather resistance, chemical resistance, low-temperature flexibility and high-temperature stability, adhesion durability and side reactions during the curing process, making it difficult to meet the heat dissipation and insulation requirements of AI chips, automotive electronics and 5G communication equipment.

Method used

By using modified organic tin catalysts, the synergistic effect of mesoporous materials and organic ligands is achieved to optimize the cross-linking network, enhance weather resistance, chemical resistance, wide temperature performance and bonding durability, and inhibit side reactions.

Benefits of technology

A high-strength thermally conductive insulating sealant with rapid surface curing has been achieved, which improves weather resistance, chemical resistance, low-temperature flexibility, high-temperature stability and bonding durability, meeting the heat dissipation and insulation requirements of electronic equipment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a rapid surface drying and curing high-strength heat-conducting insulating sealant and a preparation method thereof, and belongs to the technical field of sealing. The silicone rubber is prepared from the following components in parts by weight: 50 to 100 parts of alpha, omega-dihydroxyl polydimethylsiloxane, 10 to 50 parts of alkoxy polydimethylsiloxane, 5 to 30 parts of low-viscosity hydroxyl silicone oil, 5 to 30 parts of ultralow-viscosity hydroxyl silicone oil, 3 to 10 parts of methyl silicone oil, 5 to 20 parts of functional filler, 3 to 20 parts of coupling agent prepolymer, 50 to 100 parts of reinforcing filler, 10 to 30 parts of heat-conducting filler, 1 to 10 parts of cross-linking agent and 0.1 to 2 parts of modified organic tin catalyst. The preparation method comprises the following steps: taking the raw materials, and compounding. The sealant prepared by the preparation method disclosed by the invention meets the requirements of electronic components and power transmission devices on heat dissipation and insulation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sealant and a preparation method thereof, in particular to a high-strength thermally conductive insulating sealant with rapid surface drying and curing and a preparation method thereof, belonging to the technical field of sealing. Background Art

[0002] With the development of AI chips, automotive electronics (such as SiC / GaN devices), and 5G communications equipment, increased power density has led to a surge in heat generation. Tests have shown that for every 2°C increase in electronic component temperature, reliability decreases by 10%, and that the lifespan at a 50°C temperature rise is only one-sixth of that at a 25°C temperature rise. With the increase in 5G computing speeds, 5G mobile phone chips consume approximately 11W, about 2.5 times that of 4G phones, which will undoubtedly generate more heat. However, the size of integrated circuit chips and electronic components continues to shrink, internal structures become more compact, and the body is evolving towards non-metallic materials. The need for additional heat dissipation design to compensate for heat dissipation has become a pressing issue for electronic devices. Silicone rubber, with its excellent weather resistance and curing properties, has considerable potential for application in this field.

[0003] Since silicone sealants have the following performance and quality defects: insufficient weather resistance, limited chemical resistance, conflict between low-temperature flexibility and high-temperature stability, poor adhesion durability, and performance affected by side reactions during the curing process; the present invention compensates for the above sealant performance defects by modifying the organotin catalyst. Summary of the Invention

[0004] In order to solve the above problems, the present invention provides a high-strength thermal conductive insulating sealant with rapid surface curing and a preparation method thereof.

[0005] To achieve the above objectives, the technical solution of the present invention is: a high-strength thermally conductive insulating sealant with rapid surface drying and curing, comprising the following raw materials in parts by weight: 50-100 parts of α,ω dihydroxy polydimethylsiloxane, 10-50 parts of alkoxy polydimethylsiloxane, 5-30 parts of low-viscosity hydroxy silicone oil, 5-30 parts of ultra-low viscosity hydroxy silicone oil, 3-10 parts of methyl silicone oil, 5-20 parts of functional filler, 3-20 parts of coupling agent prepolymer, 50-100 parts of reinforcing filler, 10-30 parts of thermally conductive filler, 1-10 parts of crosslinking agent, and 0.1-2 parts of modified organic tin catalyst.

[0006] Furthermore, the functional filler is polydimethylsilicone oil; the coupling agent prepolymer is a mixture of KH560 and any one of the following: KH562, KH561, KH792, KH571, KH570, KH550, KH580, KH590; the reinforcing filler is one or more of precipitated silica, fumed silica, activated calcium carbonate, Baiyanhua, nano calcium carbonate or quartz powder; the thermal conductive filler is one or more of aluminum nitride, boron nitride, silicon carbide, silicon nitride and aluminum oxide; the crosslinking agent is one or more of tetraethyl orthosilicate, methyl orthosilicate, methyltriethoxysilane, methyltriacetoxysilane and methyltrimethoxysilane; the viscosity of the α,ω dihydroxy polydimethylsiloxane is in the range of 10000CS-100000CS.

[0007] Furthermore, KH560 and other coupling agents in the coupling agent prepolymer are mixed and pretreated in a mass ratio of 10:1-5. The pretreatment method is to react in an acidic environment with a pH of 4-6 for 20 minutes to 60 minutes, and then remove the acid water to obtain a pretreated coupling agent prepolymer. The particle size of the thermally conductive filler is 1 nm to 100 μm (that is, the thermally conductive filler of the present invention can be composed of multiple thermally conductive fillers with different particle sizes, or it can be composed of a single type of thermally conductive filler with different particle sizes). The α, ω dihydroxy polydimethylsiloxane is a mixture of low viscosity and high viscosity.

[0008] Furthermore, the modified organotin catalyst is prepared by the following steps: Step S1, reacting an organotin compound with an organic ligand containing a special functional group in an organic solvent to prepare a stable complex, wherein the organic ligand is a compound containing a carboxyl group and a long-chain alkyl group; Step S2: adding a mesoporous material with a large specific surface area and a rich pore structure to the reaction system obtained in step S1 and reacting for a period of time, filtering, washing, and drying to obtain a modified organotin catalyst.

[0009] Furthermore, in step S1, the organotin compound is dibutyltin dilaurate, dibutyltin dichloride, dibutyltin triacetate, dibutyltin oxide, dioctyltin oxide, tributyltin chloride, dibutyltin diacetate, dibutyltin maleate, tributyltin oxide or organic bismuth; the long-chain alkyl group is a long-chain alkyl group having 12-18 carbon atoms, and the weight ratio of the organic ligand to the organotin compound is 1:1-5; the reaction temperature is controlled at 50-80°C, and the reaction time is 3-5 hours; the organic solvent is any one of toluene, xylene, dichloromethane, acetone, ethyl acetate, and n-hexane, and the amount of the organic solvent added is 5%-25% of the mass of the organotin compound.

[0010] Furthermore, the organic ligand is octadecyl-polyethylene glycol-carboxyl, dodecyl polyethylene glycol carboxylic acid or 12-hydroxystearic acid; the weight ratio of the organic ligand to the organotin compound is 1:1-2; and the amount of organic solvent added is 8%-15% of the mass of the organotin compound.

[0011] Furthermore, in step S2, the amount of the mesoporous material added is 10-30% of the mass of the organotin compound, and the loading reaction is carried out under stirring at 50-90°C for 2-3 hours; the specific surface area of ​​the mesoporous material is 600-1000 m² / g.

[0012] The method for preparing the above-mentioned fast surface-curing high-strength thermal conductive insulating sealant comprises taking various raw materials according to predetermined amounts, mixing them evenly, removing low molecular weight components at high temperature, and then filling the mixture into packaging tubes for storage after the temperature reaches room temperature.

[0013] Furthermore, the high temperature is 100-150°C.

[0014] The beneficial effects of the high-strength thermally conductive insulating sealant with rapid surface curing and the preparation method thereof of the present invention are: The present invention utilizes the modified catalyst to catalyze crosslinking, and its components can serve as functional fillers or structure regulators to compensate for the performance defects of the sealant in the following aspects: 1. Improved weather resistance: physical shielding of mesoporous materials and chemical stabilization of organic ligands Mesoporous materials (such as MCM-41 molecular sieve) function as a physical barrier: Their high surface area (600-1000 m² / g) and nanoscale pore structure allow for uniform dispersion within the sealant matrix, forming a "UV scattering layer" that reduces direct UV attack on Si-O-Si bonds. Furthermore, the inert environment within the pores inhibits ozone penetration and slows oxidative degradation. Network reinforcement: Molecular sieves, as inorganic fillers, form chemical bonds with siloxane chains via coupling agents (such as γ-aminopropyltriethoxysilane), enhancing the density of the crosslinked network and reducing the diffusion rate of free radicals.

[0015] The role of organic ligands (such as 12-hydroxystearic acid): Free radical capture: The carbon-hydrogen bond in the long-chain alkyl structure can act as a "sacrificial group", preferentially reacting with free radicals in the environment to protect the main chain silicon-oxygen bond; the coordination effect of the carboxyl group and the tin atom can stabilize the active center of the catalyst and reduce the by-product free radicals produced during the catalytic process.

[0016] 2. Improved chemical resistance: network densification and adsorption of mesoporous materials Improved catalytic selectivity: The modified catalyst optimizes the electron cloud density of tin atoms through coordination, promoting regular "head-to-tail" crosslinking of silanol groups, reducing side reactions such as branching or cyclization, and increasing crosslink density by 15%-20%. This reduces network porosity and blocks the permeation pathway for media molecules. Adsorption of mesoporous materials: The pores of MCM-41 (2-5 nm) selectively adsorb small molecules (such as methanol and organic acids), reducing their concentration within the sealant and slowing swelling. Furthermore, the silanol groups on the pore surface can form hydrogen bonds with polar groups in the media, further inhibiting permeation.

[0017] 3. Wide-temperature performance optimization: synergistic toughening of organic ligands and mesoporous materials Organic ligands provide flexibility: Long-chain alkyl groups (such as 12-carbon chains) act as "molecular tougheners" interspersed within the siloxane network. At low temperatures, they hinder chain crystallization, maintain segment mobility, and lower the glass transition temperature (Tg) by 5-10°C, improving low-temperature flexibility. At high temperatures, the thermal movement of the alkyl chains buffers thermal expansion of the molecular chains, reducing network relaxation at high temperatures. Rigid support provided by mesoporous materials: The nanoscale framework of the molecular sieve remains stable at high temperatures, acting as "physical crosslinks" to limit excessive movement of the siloxane chains, preventing loss of elasticity at high temperatures and increasing the sealant's tensile strength retention at 200°C by over 30%.

[0018] 4. Enhanced bonding durability: interface anchoring and catalyst residue control Mesoporous Material Interface Anchoring: The surface hydroxyl groups of MCM-41 can form hydrogen or covalent bonds with hydroxyl groups on the surface of substrates (such as aluminum alloys and glass), effectively creating "nanoscale anchors" at the sealant-substrate interface, enhancing interfacial bonding. Simultaneously, the catalyst is loaded within the mesoporous channels, reducing the migration of free tin ions to the interface and preventing interfacial aging caused by metal ion catalysis. Catalytic Residue Control: The modified catalyst reduces the mobility of tin ions through coordination. Residual catalyst after curing exists as a stable complex, preventing hydrolysis at the sealant-substrate interface and thus slowing bond strength degradation.

[0019] 5. Side reaction inhibition: synergistic regulation of catalytic activity and selectivity Precise catalysis by coordination: The coordination bond between the organic ligand and the tin atom can regulate the activation order of the catalyst on the silanol group, preferentially catalyzing the cross-linking of the terminal hydroxyl groups, reducing the participation of the side chain hydroxyl groups in the reaction, avoiding the formation of branched structures, making the cross-linking network more regular, and reducing the internal stress, thereby improving the uniformity of mechanical properties (such as the fluctuation range of the elongation at break is reduced to ±5%).

[0020] This invention uses alkoxysilane to modify 107 silicone rubber to produce alkoxy-terminated 107 silicone rubber. By modifying an organotin catalyst and compounding it with various low-dielectric and thermally conductive fillers, a high-strength thermally conductive insulating sealant with rapid surface-curing is prepared. This thermally conductive insulating sealant is a condensed, single-component, room-temperature fast-curing silicone rubber that is easy to use, environmentally friendly, and offers excellent thermal conductivity and insulation properties, high strength, and excellent adhesion to substrates.

[0021] The sealant prepared by the present invention solves the heat dissipation needs and insulation performance requirements of electronic components and power transmission devices. The sealant prepared by the present invention is obtained by compounding various raw materials under specific ratio conditions. When used, it can be cured at room temperature. It is not restricted by the shape of the device and can be used in any scenario. It is easy to operate. It can be quickly cured at room temperature, meeting the adhesion requirements on metal substrates. It also has good adhesion to silicone rubber substrates. It can also meet the process technology requirements such as thin layer coating on silicone substrates. It can also be cured in different molds to obtain films of different shapes. The hardness of the film after curing is 20-70A, tear strength is 5-20N / mm, elongation at break is 100%-500%, and tensile strength is 1-10MPa.

[0022] The present invention prepares a high-strength thermally conductive insulating sealant that can quickly dry and cure by modifying an organic tin catalyst and compounding different low-dielectric fillers and thermally conductive fillers. The sealant has a dry-to-cure time of 3 minutes, a curing time of 10 minutes, and a thermal conductivity of 5 (W / (m·K)). DETAILED DESCRIPTION

[0023] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0024] This invention uses alkoxysilane to modify 107 silicone rubber to produce alkoxy-terminated 107 silicone rubber. By modifying an organotin catalyst and compounding it with various low-dielectric and thermally conductive fillers, a high-strength thermally conductive insulating sealant with rapid surface-curing is prepared. This thermally conductive insulating sealant is a condensed, single-component, room-temperature fast-curing silicone rubber that is easy to use, environmentally friendly, and offers excellent thermal conductivity and insulation properties, high strength, and excellent adhesion to substrates.

[0025] The present invention provides a high-strength, thermally conductive, insulating sealant with rapid surface curing, comprising the following raw materials by weight: 50-100 parts of α,ω dihydroxy polydimethylsiloxane, 10-50 parts of alkoxy polydimethylsiloxane, 5-30 parts of low-viscosity hydroxy silicone oil, 5-30 parts of ultra-low-viscosity hydroxy silicone oil, 3-10 parts of methyl silicone oil, 5-20 parts of functional filler, 3-20 parts of coupling agent prepolymer, 50-100 parts of reinforcing filler, 10-30 parts of thermally conductive filler, 1-10 parts of crosslinking agent, and 0.1-2 parts of modified organotin catalyst. This invention addresses the heat dissipation and insulation performance requirements of electronic components and power transmission devices.

[0026] Specifically, the functional filler is polydimethylsilicone oil; the coupling agent prepolymer is a mixture of KH560 and any one of the following: KH562, KH561, KH792, KH571, KH570, KH550, KH580, and KH590; the KH560 and other coupling agents in the coupling agent prepolymer are mixed and pretreated in a mass ratio of 10:1-5, and the pretreatment method is to react in an acidic environment with a pH of 4-6 for 20 minutes to 60 minutes, and then remove the acid water to obtain the pretreated coupling agent prepolymer; The viscosity of the α,ω dihydroxy polydimethylsiloxane is in the range of 10000CS-100000CS, which is a mixture of low viscosity and high viscosity; the reinforcing filler is one or more of precipitated silica, fumed silica, activated calcium carbonate, white silica, nano calcium carbonate or quartz powder; The thermally conductive filler is one or more of aluminum nitride, boron nitride, silicon carbide, silicon nitride and aluminum oxide; the particle size of the thermally conductive filler is 1 nm-100 μm; The crosslinking agent is one or more of ethyl orthosilicate, methyl orthosilicate, methyltriethoxysilane, methyltriacetoxysilane, and methyltrimethoxysilane.

[0027] The modified organotin catalyst is prepared by the following steps: Step S1, reacting an organotin compound with an organic ligand containing a special functional group in an organic solvent to prepare a stable complex, wherein the organic ligand is a compound having a carboxyl group and a long-chain alkyl group; the organotin compound is dibutyltin dilaurate, dibutyltin dichloride, dibutyltin triacetate, dibutyltin oxide, dioctyltin oxide, tributyltin chloride, dibutyltin diacetate, dibutyltin maleate, tributyltin oxide or organic bismuth; the long-chain alkyl group is a long-chain alkyl group having 12-18 carbon atoms, and the weight ratio of the organic ligand to the organotin compound is 1:1-5; the reaction temperature is controlled at 50-80°C, and the reaction time is 3-5 hours; the organic solvent is any one of toluene, xylene, dichloromethane, acetone, ethyl acetate, and n-hexane, and the amount of the organic solvent added is 5%-25% by mass of the organotin compound, preferably 8%-15%.

[0028] Step S2: Add a mesoporous material having a large specific surface area and a rich pore structure to the reaction system obtained in step S1, and after a period of reaction, filter, wash, and dry to obtain a modified organotin catalyst; the amount of the mesoporous material added is 10-30% by mass of the organotin compound, and the loading reaction is carried out at 50-90° C. under stirring conditions for 2-3 hours; the specific surface area of ​​the mesoporous material is 600-1000 m² / g.

[0029] The method for preparing a high-strength thermal conductive insulating sealant with rapid surface drying and curing is characterized in that the raw materials are taken in predetermined amounts, mixed evenly, low molecular weight materials are removed at high temperature, and the mixture is filled into a packaging tube for storage after the temperature reaches room temperature; the high temperature is 100-150°C.

[0030] Example 1

[0031] Modified catalyst preparation Dissolve 10 g of dibutyltin dilaurate in 80 mL of toluene, add 12 g of C18-PEG12-COOH, and react at 60°C for 4 h. Add 3 g of MCM-41 molecular sieves, stir for 2 h, and filter and dry to obtain the modified catalyst.

[0032] Sealant preparation A sealant was prepared by mixing the following ingredients in parts by weight: 60 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 5 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 5 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 5 parts of coupling agent prepolymer (the mass ratio of KH560 prepolymer to KH550 is 10:1), 50 parts of activated calcium carbonate, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is aluminum nitride with a particle size in the range of 1 nm-100 μm), 25 parts of fumed silica, 5 parts of ethyl orthosilicate, and 0.3 parts of a modified organic tin catalyst.

[0033] Performance After 500 hours of UV aging, the tensile strength retention rate is 92%; it can withstand 10% hydrochloric acid solution for 7 days with a swelling rate of only 2%, reflecting the improvement of weather resistance and chemical resistance.

[0034] Example 2

[0035] Modified catalyst preparation 12g of dioctyltin oxide and 15g of 12-hydroxystearic acid were reacted in xylene at 70°C for 3.5h.

[0036] 4 g of SBA-15 mesoporous material was added and loaded for 3 h to obtain a modified catalyst.

[0037] Sealant preparation A sealant was prepared by mixing, in parts by weight, 55 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 30 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 5 parts of methyl silicone oil, 20 parts of polydimethyl silicone oil, 20 parts of coupling agent prepolymer (wherein the mass ratio of KH560 prepolymer to KH570 is 10:5), 50 parts of activated calcium carbonate, 10 parts of thermally conductive filler (in this embodiment, the thermally conductive filler is boron nitride with a particle size of 1 nm-100 μm), 30 parts of precipitated silica, 5 parts of ethyl orthosilicate, and 0.25 parts of a modified organotin catalyst.

[0038] Performance There is no crack when bent at -50℃, and the elasticity is maintained well when placed at 200℃ for 24 hours, showing excellent wide temperature performance.

[0039] Example 3

[0040] Modified catalyst preparation 8g of tributyltin chloride and 10g of α-carboxyl long-chain alkyl dimethylamine oxide were reacted in acetone at 55°C for 5h. 2.5g of MCM-48 molecular sieves were added and stirred for 2.5h to obtain a modified catalyst.

[0041] Sealant preparation A sealant was prepared by mixing, in parts by weight, 65 parts of α,ω dihydroxy polydimethylsiloxane, 10 parts of alkoxy polydimethylsiloxane, 10 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 3 parts of methyl silicone oil, 10 parts of polydimethyl silicone oil, 10 parts of coupling agent prepolymer (wherein the mass ratio of KH560 prepolymer to KH550 is 10:2), 50 parts of nano-calcium carbonate, 30 parts of thermally conductive filler (in this embodiment, the thermally conductive filler is silicon carbide with a particle size of 1 nm-100 μm), 30 parts of precipitated silica, 10 parts of methyl orthosilicate, and 0.4 parts of a modified organotin catalyst.

[0042] Performance The bonding strength to the glass substrate reaches 3.0MPa. After 5 wet-heat cycles, the bonding strength does not decrease significantly, which reflects the enhanced bonding durability.

[0043] Example 4

[0044] Modified catalyst preparation 15 g of dibutyltin diacetate was reacted with 18 g of C12-PEG-COOH in ethyl acetate at 65°C for 4 h. 5 g of Al-MCM-41 molecular sieve was added and the reaction was continued for 3 h. The modified catalyst was then dried.

[0045] Sealant preparation A sealant was prepared by mixing, by weight, 58 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 20 parts of low-viscosity hydroxy silicone oil, 30 parts of ultra-low-viscosity hydroxy silicone oil, 8 parts of methyl silicone oil, 15 parts of polydimethyl silicone oil, 15 parts of coupling agent prepolymer (wherein the mass ratio of KH560 prepolymer to KH561 is 10:2), 50 parts of activated calcium carbonate, 25 parts of thermally conductive filler (in this embodiment, the thermally conductive filler is silicon nitride with a particle size in the range of 1 nm-100 μm), 28 parts of fumed silica, 8 parts of methyltriethoxysilane, and 0.35 parts of a modified organotin catalyst.

[0046] Performance The catalytic cross-linking side reaction was reduced by 40%, the internal stress of the sealant was reduced after curing, and the tensile strength was increased to 4.8MPa, proving that the side reaction was effectively suppressed.

[0047] Example 5

[0048] Modified catalyst preparation 10g of dibutyltin maleate was reacted with 13g of a long-chain compound containing carboxyl and hydroxyl groups in toluene-ethyl acetate (volume ratio 3:1) at 60°C for 4.5h. 3.5g of MCM-41 molecular sieves was added, stirred for 2h, and filtered to dryness.

[0049] Sealant preparation A sealant was prepared by mixing, in parts by weight, 62 parts of α,ω dihydroxy polydimethylsiloxane, 50 parts of alkoxy polydimethylsiloxane, 25 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 5 parts of methyl silicone oil, 8 parts of polydimethyl silicone oil, 15 parts of coupling agent prepolymer (wherein the mass ratio of KH560 prepolymer to KH562 is 10:4), 50 parts of nano-titanium dioxide, 20 parts of thermally conductive filler (in this embodiment, the thermally conductive filler is aluminum oxide with a particle size in the range of 1 nm-100 μm), 30 parts of precipitated silica, 4 parts of methyltriacetoxysilane, and 0.3 part of a modified organic tin catalyst.

[0050] Performance The mesoporous material absorbs ultraviolet rays, and the organic ligands capture free radicals, which significantly improves weather resistance. There is no powdering after 1000 hours of UV aging.

[0051] Example 6

[0052] Modified catalyst preparation 12g of tributyltin oxide was reacted with 16g of C18-PEG12-COOH in n-hexane at 75°C for 3h. 4g of SBA-15 mesoporous material was added and loaded for 2.5h.

[0053] Sealant preparation A sealant was prepared by mixing, by weight, 56 parts of α,ω dihydroxy polydimethylsiloxane, 35 parts of alkoxy polydimethylsiloxane, 30 parts of low-viscosity hydroxy silicone oil, 30 parts of ultra-low-viscosity hydroxy silicone oil, 3 parts of methyl silicone oil, 20 parts of polydimethyl silicone oil, 8 parts of coupling agent prepolymer (wherein the mass ratio of KH560 prepolymer to KH570 is 10:5), 50 parts of nano-calcium carbonate, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is a mixture of aluminum nitride and boron nitride with a particle size of 1 nm-100 μm), 22 parts of precipitated silica, 5 parts of ethyl orthosilicate, and 0.4 parts of a modified organic tin catalyst.

[0054] Performance The bonding strength to aluminum alloy substrates is long-lasting and after 1000h of salt spray test, the bonding strength remains above 85%.

[0055] Example 7

[0056] Modified catalyst preparation 9 g of dibutyltin dilaurate and 11 g of 12-hydroxystearic acid were reacted in dichloromethane at 50°C for 5 h. 3 g of MCM-48 molecular sieves were added, stirred for 2 h, and dried to obtain the modified catalyst.

[0057] Sealant preparation A sealant was prepared by mixing, by weight, 63 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 5-30 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 10 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 15 parts of coupling agent prepolymer (wherein the mass ratio of KH560 prepolymer to KH571 is 10:3), 30 parts of nano-calcium carbonate, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is a mixture of aluminum nitride and silicon nitride with a particle size in the range of 100 nm-10 μm), 30 parts of precipitated silica, 5 parts of ethyl orthosilicate, and 0.32 parts of a modified organotin catalyst.

[0058] Performance The network is dense, resistant to diesel immersion for 7 days, with a swelling rate of only 3%, and excellent resistance to chemical media.

[0059] Example 8

[0060] Modified catalyst preparation 14g of dioctyltin oxide was reacted with 17g of α-carboxyl long-chain alkyl dimethylamine oxide in toluene at 80°C for 3.5h. 4.5g of Al-MCM-41 molecular sieve was added and loaded for 3h.

[0061] Sealant preparation A sealant was prepared by mixing the following ingredients in parts by weight: 57 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 5 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 10 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 10 parts of coupling agent prepolymer (the mass ratio of KH560 prepolymer to KH590 is 10:2), 50 parts of nano-calcium carbonate, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is aluminum nitride with a particle size in the range of 100 nm-1 μm), 26 parts of fumed silica, 5 parts of ethyl orthosilicate, and 0.27 parts of a modified organic tin catalyst.

[0062] Performance Wide temperature performance is optimized, and the sealant will not crack or deform after 10 cycles from -60℃ to 220℃.

[0063] Example 9

[0064] Modified catalyst preparation 11g of tributyltin chloride was reacted with 14g of C12-PEG-COOH in acetone-n-hexane (volume ratio 1:1) at 65°C for 4h. 3.2g of SBA-15 mesoporous material was added and stirred for 2.5h.

[0065] Sealant preparation A sealant was prepared by mixing, in parts by weight, 60 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 10 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 7 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 20 parts of coupling agent prepolymer (wherein the mass ratio of KH560 prepolymer to KH580 is 10:1), 40 parts of nano-titanium dioxide, 10 parts of thermally conductive filler (in this embodiment, the thermally conductive filler is silicon carbide with a particle size in the range of 1-100 μm), 26 parts of fumed silica, 5 parts of ethyl orthosilicate, and 0.33 parts of a modified organic tin catalyst.

[0066] Performance The catalytic selectivity is improved, the side reaction products are reduced, the sealant modulus is uniform, and the elongation at break reaches 450%.

[0067] Example 10 Modified catalyst preparation 13g of dibutyltin diacetate was reacted with 16g of a long-chain compound containing carboxyl and hydroxyl groups in ethyl acetate at 70°C for 3.5h. 4g of MCM-41 molecular sieve was added and the reaction was continued for 3h. The modified catalyst was then dried.

[0068] Sealant preparation A sealant was prepared by mixing, by weight, 58 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 30 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 8 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 8 parts of coupling agent prepolymer (the mass ratio of KH560 prepolymer to KH570 is 10:3), 40 parts of nano-titanium dioxide, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is aluminum oxide with a particle size in the range of 10-100 μm), 24 parts of precipitated silica, 5 parts of ethyl orthosilicate, and 0.29 parts of a modified organic tin catalyst.

[0069] Performance The mesoporous material anchors the interface, and the organic ligand reduces catalyst residue, providing long-lasting and stable adhesion to the stainless steel substrate.

[0070] Example 11 Modified catalyst preparation 10 g of dibutyltin maleate was reacted with 12 g of C18-PEG12-COOH in toluene at 60°C for 4 h.

[0071] Add 3.5 g of MCM-48 molecular sieves and stir for 2.5 h.

[0072] Sealant preparation A sealant was prepared by mixing, in parts by weight, 62 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 5 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 3 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 3 parts of coupling agent prepolymer (the mass ratio of KH560 prepolymer to KH571 is 10:5), 30 parts of nano-calcium carbonate, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is silicon nitride with a particle size in the range of 10-100 nm), 26 parts of fumed silica, 5 parts of ethyl orthosilicate, and 0.31 parts of a modified organic tin catalyst.

[0073] Performance Weather resistance is significantly improved. After 1000h of UV aging, the tensile strength remains at 90% with no noticeable changes on the surface.

[0074] Example 12 Modified catalyst preparation 12g of tributyltin oxide and 15g of 12-hydroxystearic acid were reacted in xylene at 75°C for 3h. 4.2g of SBA-15 mesoporous material was added and loaded for 2.8h.

[0075] Sealant preparation A sealant was prepared by mixing, by weight, 56 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 10 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 10 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 10 parts of coupling agent prepolymer (wherein the mass ratio of KH560 prepolymer to KH792 is 10:4), 40 parts of nano-titanium dioxide, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is a mixture of silicon nitride and boron nitride with a particle size in the range of 100 nm-100 μm), 27 parts of precipitated silica, 5 parts of ethyl orthosilicate, and 0.26 parts of a modified organic tin catalyst.

[0076] Performance Excellent wide temperature performance, the sealant's elasticity and bonding properties are stable in an environment of -55℃ to 210℃.

[0077] Example 13 Modified catalyst preparation 9g of dibutyltin dilaurate and 11g of α-carboxyl long-chain alkyl dimethylamine oxide were reacted in dichloromethane at 55°C for 5h. 3g of Al-MCM-41 molecular sieves were added and stirred for 2h.

[0078] Sealant preparation A sealant was prepared by mixing, by weight, 63 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 5 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 4 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 15 parts of coupling agent prepolymer (the mass ratio of KH560 prepolymer to KH562 is 10:3), 30 parts of nano-titanium dioxide, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is a mixture of silicon carbide and silicon nitride with a particle size in the range of 1 nm-100 μm), 26 parts of fumed silica, 5 parts of ethyl orthosilicate, and 0.34 parts of a modified organic tin catalyst.

[0079] Performance Excellent resistance to chemical media, resistant to 10% sodium hydroxide solution for 7 days, with a swelling rate of only 2.5%.

[0080] Example 14 Modified catalyst preparation 14g dioctyltin oxide and 17g C 12 -PEG-COOH was reacted in toluene-ethyl acetate (volume ratio 2:1) at 65°C for 4.5 h. 4.5 g of MCM-41 molecular sieves was added and loaded for 3 h.

[0081] Sealant preparation A sealant was prepared by mixing the following ingredients in parts by weight: 57 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 25 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 5 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 15 parts of coupling agent prepolymer (the mass ratio of KH560 prepolymer to KH561 is 10:5), 40 parts of nano-titanium dioxide, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is a mixture of silicon carbide and silicon nitride with a particle size in the range of 1 nm-100 μm), 23 parts of fumed silica, 5 parts of ethyl orthosilicate, and 0.28 parts of a modified organic tin catalyst.

[0082] Performance The bonding durability is enhanced. After bonding to the glass substrate, the bonding strength is maintained at 88% after 8 wet-heat cycles.

[0083] Example 15 Modified catalyst preparation 11g of tributyltin chloride was reacted with 14g of a long-chain compound containing carboxyl and hydroxyl groups in acetone at 70°C for 3.8h. 3.3g of SBA-15 mesoporous material was added and stirred for 2.6h.

[0084] Sealant preparation A sealant was prepared by mixing the following ingredients in parts by weight: 60 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 10 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 10 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 5 parts of coupling agent prepolymer (wherein the mass ratio of KH560 prepolymer to KH550 is 10:1), 35 parts of nano-calcium carbonate, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is a mixture of silicon carbide and silicon nitride with a particle size in the range of 1 nm-100 μm), 26 parts of fumed silica, 5 parts of ethyl orthosilicate, and 0.32 parts of a modified organic tin catalyst.

[0085] Performance The side reaction inhibition effect is obvious, the internal structure of the sealant is uniform after curing, and the mechanical properties are improved by 20%.

[0086] Comparative Example 1: Unmodified catalyst Catalyst preparation 10 g of dibutyltin dilaurate was used directly as a catalyst.

[0087] Sealant preparation A sealant was prepared by mixing the following ingredients in parts by weight: 60 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 5 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 5 parts of low-viscosity hydroxy silicone oil, 5 parts of polydimethylsiloxane, 5 parts of coupling agent prepolymer (the mass ratio of KH560 prepolymer to KH550 is 10:1), 50 parts of activated calcium carbonate, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is aluminum nitride with a particle size in the range of 1 nm-100 μm), 25 parts of fumed silica, 5 parts of ethyl orthosilicate, and 0.3 parts of an unmodified organotin catalyst.

[0088] Performance After 200 hours of UV aging, the tensile strength dropped to 60%; the swelling rate reached 15% after 3 days of resistance to 10% hydrochloric acid solution. All performances were significantly lower than those in Example 1.

[0089] Comparative Example 2: No mesoporous material loading Modified catalyst preparation 10 g of dibutyltin dilaurate was dissolved in 80 mL of toluene, 12 g of C18-PEG12-COOH was added, and the mixture was reacted at 60°C for 4 h without adding MCM-41 molecular sieves.

[0090] Sealant preparation The sealant preparation method is the same as that of Example 1.

[0091] Performance Weather resistance has decreased significantly. After 500 hours of UV aging, the tensile strength retention rate is only 70%. The chemical resistance has decreased. After 7 days of resistance to 10% hydrochloric acid solution, the swelling rate reaches 8%.

[0092] Comparative Example 3: No organic ligand modification Modified catalyst preparation 10 g of dibutyltin dilaurate was dissolved in 80 mL of toluene, 3 g of MCM-41 molecular sieves were added, and the mixture was stirred for 2 h. No C18-PEG12-COOH was added.

[0093] Sealant preparation The sealant preparation method is the same as that of Example 1.

[0094] Performance The wide temperature performance is poor, and brittle cracks occur at low temperatures of -30°C; the bonding durability is poor, and the bonding strength of the glass substrate drops to 50% after 3 wet-heat cycles.

[0095] Comparative Example 4: Traditional Catalyst Replacement Catalyst preparation 5 g of organobismuth catalyst was used instead of the modified organotin catalyst.

[0096] Sealant preparation A sealant was prepared by mixing the following ingredients in parts by weight: 60 parts of α,ω dihydroxy polydimethylsiloxane, 20 parts of alkoxy polydimethylsiloxane, 5 parts of low-viscosity hydroxy silicone oil, 10 parts of ultra-low-viscosity hydroxy silicone oil, 5 parts of methyl silicone oil, 5 parts of polydimethyl silicone oil, 5 parts of coupling agent prepolymer (the mass ratio of KH560 prepolymer to KH550 is 10:1), 50 parts of activated calcium carbonate, 10 parts of thermally conductive filler (the thermally conductive filler in this embodiment is aluminum nitride with a particle size in the range of 1 nm-100 μm), 25 parts of fumed silica, 5 parts of ethyl orthosilicate, and 0.3 parts of an organic bismuth catalyst.

[0097] Performance The curing speed is greatly slowed down, and the surface drying time is extended to 80 minutes; the tensile strength is only 3.0 MPa, and the elongation at break is 250%. The comprehensive performance is far lower than that of Example 1.

[0098] Comparative Example 5: Imbalanced Modified Catalyst Modified catalyst preparation Dissolve 10g of dibutyltin dilaurate in 80mL of toluene, add 25g of C18-PEG12-COOH (excess organic ligand), and react at 60°C for 4h. Add 3g of MCM-41 molecular sieves, stir for 2h, and filter to dry to obtain the modified catalyst.

[0099] Sealant preparation The sealant preparation method is the same as that of Example 1.

[0100] Performance The catalytic activity is reduced and the curing is incomplete; the sealant's resistance to chemical media is reduced, and it can withstand 10% hydrochloric acid solution for 7 days, with a swelling rate of 10%, and the internal structure is loose, with a tensile strength of only 3.5MPa.

[0101] The specific test condition parameters of each test index in the above embodiments and comparative examples are as follows: 1. UV resistance test Referring to ASTM G154, "Test Method for Exposure of Nonmetallic Materials to Ultraviolet Light from Fluorescent Devices," a UVA-340 lamp was used to simulate ultraviolet radiation from sunlight, with an irradiance of 0.89 W / m² and a wavelength of 340 nm. Sealant samples were irradiated with UV light for 8 hours at a black panel temperature of (60±3)°C, followed by condensation at a black panel temperature of (50±3)°C for 4 hours, and this cycle repeated. After 1000 hours of exposure, the tensile strength, color, and surface condition of the samples before and after irradiation were compared. For example, in Example 1, the sealant exhibited a tensile strength retention of 92% after 500 hours of UV aging, determined by comparing the tensile strength test value after aging with the initial tensile strength. Color changes were compared with color charts, and the surface condition was observed using a 5x magnifying glass for signs of chalking and cracking.

[0102] 2. Hydrochloric acid solution resistance test The sealant was tested using a similar principle to GB / T 15728-2021, "Gravimetric test method and classification of glass resistance to boiling hydrochloric acid." A sample of the sealant with an area of ​​approximately 100 cm² was placed in a boiling 6 mol / L hydrochloric acid solution for 6 hours. After removal, the sample was rinsed with distilled water, dried in a 150°C oven for 45 minutes, and accurately weighed after cooling. Hydrochloric acid resistance is measured by swelling ratio: swelling ratio = (m2 - m1) / m1 × 100%, where m1 is the initial mass and m2 is the mass after immersion. As in Example 7, the swelling ratio after 7 days of diesel immersion was only 3%. The same principle applies when the diesel is replaced with a hydrochloric acid solution.

[0103] 3. Low temperature bending test According to GB / T 18426-2021 "Low-Temperature Bend Test for Rubber- or Plastic-Coated Fabrics," after conditioning the sealant sample, place it in a low-temperature chamber and maintain it at the specified low temperature (e.g., -50°C) for 4 hours. Immediately after removal, place it on a bending rack, allowing the bending plate to fall freely to apply a bending force to the sample. Then, use a 5x magnifying glass to inspect the sealant coating for breaks or cracks. As shown in Example 2, no cracks were observed during bending at -50°C, indicating that the sealant exhibits good bending resistance at this low temperature.

[0104] 4. Elasticity testing Dynamic mechanical analysis (DMA) can be used in accordance with ASTM D4065, "Standard Test Method for Dynamic Mechanical Analysis of Rubber Properties." Sealant specimens are subjected to sinusoidal stress loading over a range of frequencies and temperatures, and the strain response is measured. Elasticity is assessed by calculating the storage modulus (E'), loss modulus (E''), and dissipation factor (tan δ). For example, at a specific temperature, a high storage modulus indicates good elasticity, while a low dissipation factor indicates minimal energy loss and strong elastic recovery.

[0105] 5. Bond strength test According to GB / T 7124 "Determination of tensile shear strength of adhesives (rigid material to rigid material)", the sealant is evenly applied to two substrates of specified dimensions (such as glass or metal) and cured according to the prescribed process. Using a universal testing machine, tensile and shear forces are applied to the bonded parts at a constant rate. The maximum load at failure is recorded, and the bond strength is calculated using the formula: Bond strength = maximum load / bonded area. For example, in Example 3, the bond strength to the glass substrate reached 3.0 MPa, as determined by this test method.

[0106] 6. Humidity and heat cycle test Referencing the damp heat cycle section of ASTM D4587, "Test Method for Exposure of Paint and Related Coatings to Fluorescent Ultraviolet Condensation," sealant specimens are maintained at (40±2)°C and (95±3)% relative humidity for 12 hours, followed by drying at (60±2)°C for 12 hours. Each cycle constitutes one cycle. After a specified number of cycles (e.g., 5 or 8), properties such as bond strength and tensile strength are tested. For example, in Example 10, the bond stability after multiple damp heat cycles on a stainless steel substrate was evaluated by comparing the relevant properties before and after the cycles.

[0107] 7. Cross-linking side reaction test Through infrared spectroscopy (FT-IR) and nuclear magnetic resonance (NMR) analysis, the sealant samples were tested before and after curing. The peak intensities and shifts of characteristic functional groups before and after curing were compared to determine the extent of cross-linking side reactions. If the intensity of a characteristic peak weakened or disappeared after curing, a side reaction may have occurred. Gas chromatography-mass spectrometry (GC-MS) was also used to analyze the types and amounts of side reaction products. For example, the 40% reduction in catalytic cross-linking side reactions in Example 4 was confirmed by these instrumental analyses.

[0108] 8. Internal stress test X-ray diffraction (XRD) residual stress testing was performed according to GB / T 7704, "Non-destructive testing - Determination of residual stresses by X-ray diffraction method." The sealant sample was irradiated with X-rays, the shift of the diffraction lines was measured, and the lattice strain was calculated using Bragg's law to obtain the internal stress value. As shown in Example 4, this method showed a decrease in the internal stress of the sealant after curing.

[0109] 9. Tensile strength test According to GB / T 528 "Determination of tensile stress-strain properties of vulcanized or thermoplastic rubber", the sealant is made into dumbbell-shaped samples, and a universal material testing machine is used to stretch the samples at a specified stretching rate (such as 500 mm / min), and the maximum force value when the sample breaks is recorded. Tensile strength = maximum force value / initial cross-sectional area of the sample. The tensile strength data in each example is tested according to this standard method.

[0110] 10. Elongation at break test At the same time as the tensile strength test, during the stretching process, the elongation of the sample at break is recorded using an extensometer or displacement sensor. Elongation at break = (gauge length at break - initial gauge length) / initial gauge length x 100%. For example, if the sealant in Example 9 has an elongation at break of 450%, it is calculated according to this formula.

[0111] 11. Salt spray test According to GB / T 10125 "Salt spray test for artificial atmosphere corrosion testing", a 5% sodium chloride solution is used to adjust the pH value to 6.5-7.2, and the sealant sample is continuously sprayed in a salt spray test chamber with a temperature control of (35±2)℃. After reaching the specified time (such as 1000h), observe the surface corrosion of the sample and evaluate the salt spray resistance, such as the test of the adhesion strength retention of the sealant on the aluminum alloy substrate after 1000h of salt spray test in Example 6.

[0112] 12. Modulus test Elastic modulus testing can refer to GB / T 22315-2008 "Metallic materials - Test methods for elastic modulus and Poisson's ratio" similar method, for the viscoelastic material such as sealant, use dynamic mechanical analyzer (DMA) to test under small strain condition. By measuring the slope of the stress-strain curve, the elastic modulus is calculated. Modulus data at different temperatures can reflect the wide temperature performance of the sealant, such as the modulus change after -60℃ to 220℃ cycle in Example 8, which can evaluate the performance stability of the sealant in this temperature range.

[0113] 13. Catalyst residue test Inductively coupled plasma mass spectrometry (ICP-MS) or atomic absorption spectrometry (AAS) is used. After digestion treatment of the sealant sample, the content of the catalyst metal element (such as tin element) is detected by the instrument, compared with the initial addition amount, the proportion of catalyst residue is obtained, and the catalyst residue is judged, such as the method in Example 10 to determine that the organic ligand reduces the catalyst residue.

[0114] 14. Incomplete curing detection Initial assessments were made by observing the sealant's appearance, such as surface tack and insufficient hardness. Differential scanning calorimetry (DSC) was then used according to ASTM D3418, "Standard Test Method for Transition Temperatures and Enthalpies of Polymers." The DSC curve was analyzed to determine if an unreacted curing peak was present, indicating incomplete curing. Incomplete curing, as observed in Comparative Example 5, was readily apparent from the DSC curve.

[0115] Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

Claims

1. A high-strength thermal conductive insulating sealant that quickly cures and cures, characterized in that: The invention comprises the following raw materials in parts by weight: 50-100 parts of α,ω dihydroxy polydimethylsiloxane, 10-50 parts of alkoxy polydimethylsiloxane, 5-30 parts of low-viscosity hydroxy silicone oil, 5-30 parts of ultra-low-viscosity hydroxy silicone oil, 3-10 parts of methyl silicone oil, 5-20 parts of functional filler, 3-20 parts of coupling agent prepolymer, 50-100 parts of reinforcing filler, 10-30 parts of thermal conductive filler, 1-10 parts of cross-linking agent, and 0.1-2 parts of modified organic tin catalyst.

2. The high-strength thermal conductive insulating sealant with rapid surface curing according to claim 1, characterized in that: The functional filler is polydimethylsilicone oil; the coupling agent prepolymer is a mixture of KH560 and any one of the following: KH562, KH561, KH792, KH571, KH570, KH550, KH580, KH590; the reinforcing filler is one or more of precipitated silica, fumed silica, activated calcium carbonate, Baiyanhua, nano calcium carbonate or quartz powder; the thermal conductive filler is one or more of aluminum nitride, boron nitride, silicon carbide, silicon nitride and aluminum oxide; the cross-linking agent is one or more of tetraethyl orthosilicate, methyl orthosilicate, methyltriethoxysilane, methyltriacetoxysilane and methyltrimethoxysilane; the viscosity of the α,ω dihydroxy polydimethylsiloxane is in the range of 10000CS to 100000CS.

3. The high-strength thermal conductive insulating sealant with rapid surface curing according to claim 2, characterized in that: The KH560 and other coupling agents in the coupling agent prepolymer are mixed and pretreated in a mass ratio of 10:1-5. The pretreatment method is to react in an acidic environment with a pH of 4-6 for 20 minutes to 60 minutes, and then remove the acid water to obtain the pretreated coupling agent prepolymer. The particle size of the thermal conductive filler is 1 nm to 100 μm. The α, ω dihydroxy polydimethylsiloxane is a mixture of low viscosity and high viscosity.

4. A high-strength thermally conductive insulating sealant with rapid surface curing according to any one of claims 1 to 3, characterized in that: The modified organotin catalyst is prepared by the following steps: Step S1, reacting an organotin compound with an organic ligand containing a special functional group in an organic solvent to prepare a stable complex, wherein the organic ligand is a compound containing a carboxyl group and a long-chain alkyl group; Step S2: adding a mesoporous material with a large specific surface area and a rich pore structure to the reaction system obtained in step S1 and reacting for a period of time, filtering, washing, and drying to obtain a modified organotin catalyst.

5. The high-strength thermal conductive insulating sealant with rapid surface curing according to claim 4, characterized in that: In step S1, the organotin compound is dibutyltin dilaurate, dibutyltin dichloride, dibutyltin triacetate, dibutyltin oxide, dioctyltin oxide, tributyltin chloride, dibutyltin diacetate, dibutyltin maleate, tributyltin oxide or organic bismuth; the long-chain alkyl group is a long-chain alkyl group with 12-18 carbon atoms, and the weight ratio of the organic ligand to the organotin compound is 1:1-5; the reaction temperature is controlled at 50-80°C, and the reaction time is 3-5 hours; the organic solvent is any one of toluene, xylene, dichloromethane, acetone, ethyl acetate, and n-hexane, and the amount of the organic solvent added is 5%-25% of the mass of the organotin compound.

6. The high-strength thermal conductive insulating sealant with rapid surface curing according to claim 5, characterized in that: The organic ligand is octadecyl-polyethylene glycol-carboxyl, dodecyl polyethylene glycol carboxylic acid or 12-hydroxystearic acid; the weight ratio of the organic ligand to the organotin compound is 1:1-2; and the amount of the organic solvent added is 8%-15% of the mass of the organotin compound.

7. The high-strength thermal conductive insulating sealant with rapid surface curing according to claim 4, characterized in that: In step S2, the amount of the mesoporous material added is 10-30% of the mass of the organotin compound, and the loading reaction is carried out at 50-90°C under stirring conditions for 2-3 hours; the specific surface area of ​​the mesoporous material is 600-1000 m² / g.

8. The method for preparing the high-strength thermal conductive insulating sealant with rapid surface curing according to any one of claims 1 to 7, characterized in that: Take the raw materials according to the predetermined amount, mix them evenly, remove the low molecular weight at high temperature, and then fill them into packaging tubes for storage after the temperature reaches room temperature.

9. The preparation method according to claim 8, characterized in that The high temperature is 100-150°C.